effect of Varying Thickness and Artificial Aging on Color and Translucency of Cubic Zirconia and Lithium Disilicate Ceramics - El khayat, Heba Ahmed Hassan; Katamish, Hesham; Etreby, Amr; Aboushahba, Mostafa (2019)
Includes Arabic Summary.
Supervisors : Hesham Katamish, Amr Etreby, Mostafa Aboushahba.
Thesis (M.Sc.)-Future university,faculty of oral and dental medicine, 2019.
Includes bibliographical references.
Keywords: prosthodontics; Dental Implants; Oral Surgery